Effects of Dietary Prebiotic, Probiotic, and Synbiotic Supplementation on Growth Performance, Carcass Traits, Digestive Enzymes and Some Biochemical Parameters in Broiler Chickens - Olmez, M; Şahin, T; Karadağoğlu, Ö; Öğün, M; Adıgüzel Işık, S; Boğa Kuru, B; Yörük, MA (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was conducted to determine and compare the effects of chitosan-oligosaccharide (COS), probiotics (Pro), and their combination on the growth performance, carcass parameters, digestive enzymes, and serum biochemical parameters of broiler chickens. A total of 300 one-day-old mixed-sex Ross 308 broiler chicks were randomly divided into four treatment groups with five replicates each (15 chicks per replicate). No supplements were added to the basal diet in the control group; however, 1 g/kg COS, 1 g/kg Pro, and 1 g/kg COS + 1 g/kg Pro (Syn) were added to the basal diet of the respective treatment groups. At the end of the study, the results showed that the dietary supplementation of COS, Pro, and Syn significantly increased the average daily gain (P < 0.001) and average feed intake (P < 0.001) in all the treatment groups compared to the control group. COS supplemented group showed the lowest feed conversion ratio (P = 0.004) among all the study groups. There was no significant difference between the groups for carcass parameters and internal organ weights (P > 0.05), except for live weight at slaughter, which was found to be higher in all dietary-supplemented treatment groups than in the control group. There was no significant effect (P > 0.05) of the different diets on digestive enzymes and serum biochemical parameters among the treatment groups (P > 0.05). In conclusion, dietary supplementation of COS and Pro individually and in combination with broiler diets improves performance parameters without adverse effects on serum metabolites and digestive enzymes.